Thermal Characteristic Evaluation of Different Ascorbic Acid Crystal Habits - Shajaratul Jahriah, Hassan; Fatmawati, Adam; M. R., Abu Bakar (Universiti Malaysia Pahang, 2018)
Melting temperature (Tmelt) and enthalpy of fussion (ΔHf) are important parameters to determine the quality and the thermal stability of active pharmaceutical ingredient (API) crystals. In this study, different habit of ascorbic acid was prepared by using different polar solvents namely water, methanol, ethanol and 2-propanol. Ascorbic acid crystal was then been physically and thermally characterized by using microscopic analysis, thermo gravimetric analysis (TGA) and differential scanning calometry analysis (DSC). This provides an insight into the formation of crystal habit across four different polar protic solvents. The ascorbic acid is found to grow as a cubic or prism crystal when grown in water that provides high hydrogen bond between solvent and solute. As the polarity of the solvents decrease, the hydrogen bond weaken and the width of the crystal become narrower, forming almost a needle like crystal. The thermal stability of ascorbic acid crystal is found to be the most stable when ascorbic acid is crystallized from water (prism) and the weakest from 2-Propanol (needle) due to the molecule arrangement in crystal lattice in which resulted from decreasing intermolecular forces in the liquid phase.